Heuristic Planning in Adversarial Dynamic Domains - Chamberland, Simon; Kabanza, Froduald (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
Agents in highly dynamic adversarial domains, such as RTS games, must continually make time-critical decisions to adapt their behaviour to the changing environment. In such a context, the planning agent must consider his opponent’s actions as uncontrollable, or at best influenceable. In general nondeterministic domains where there is no clear turn-taking protocol, most heuristic search methods to date do not explicitly reason about the opponent’s actions when guiding the state space exploration towards goal or high-reward states. In contrast, we are investigating a domain-independent heuristic planning approach which reasons about the dynamics and uncontrollability of the opponent’s behaviours in order to provide better guidance to the search process of the planner. Our planner takes as input the opponent’s behaviours recognized by a plan recognition module and uses them to identify opponent’s actions that lead to low-utility projected states. We believe such explicit heuristic reasoning about the potential behaviours of the opponent is crucial when planning in adversarial domains, yet is missing in today’s planning approaches.